Pilot-RCT of an integrative group therapy for patients with refractory irritable bowel syndrome (ISRCTN02977330) - Berens, Sabrina; Stroe-Kunold, Esther; Kraus, Felicitas; Tesarz, Jonas; Gauss, Annika; Niesler, Beate; Herzog, Wolfgang (Journal of psychosomatic research, 2017)
Objective Different forms of psychotherapeutic treatments have been proven effective in irritable bowel syndrome (IBS), but disorder-oriented and integrative concepts are still rare. Therefore, we implemented and evaluated an integrative group therapeutic concept within an interdisciplinary tertiary care clinic for functional gastrointestinal disorders (FGIDs). Aims: present our integrative group concept, assess feasibility issues, and evaluate efficacy
Gesehen am 18.04.2018